Monolithically, widely tunable quantum cascade lasers based on a heterogeneous active region design - Zhou, Wenjia (Sci Rep, 2016)
Quantum cascade lasers (QCLs) have become important laser sources for accessing the mid-infrared (mid-IR) spectral range, achieving watt-level continuous wave operation in a compact package at room temperature. However, up to now, wavelength tuning, which is desirable for most applications, has relied on external cavity feedback or exhibited a limited monolithic tuning range. Here we demonstrate a widely tunable QCL source over the 6.2 to 9.1 μm wavelength range with a single emitting aperture by integrating an eight-laser sampled grating distributed feedback laser array with an on-chip beam combiner. The laser gain medium is based on a five-core heterogeneous QCL wafer. A compact tunable laser system was built to drive the individual lasers within the array and produce any desired wavelength within the available spectral range. A rapid, broadband spectral measurement (520 cm(−1)) of methane using the tunable laser source shows excellent agreement to a measurement made using a standard low-speed infrared spectrometer. This monolithic, widely tunable laser technology is compact, with no moving parts, and will open new opportunities for MIR spectroscopy and chemical sensing.